EVALUASI PELAKSANAAN KESIAPSIAGAAN BENCANA BANJIR DI KABUPATEN BANDUNG - Valentina, Sela Pebri; Ilham, Muh; Tefa, Gradiana (Institut Pemerintahan Dalam Negeri, 2024)
Flood disasters are a challenge for every region, including Bandung Regency. The Bandung Regency Regional Disaster Management Agency (BPBD) seeks to reduce the risk of flood disasters through prevention and preparedness. The purpose of this study was to determine the Evaluation of the Implementation of Flood Disaster preparedness in Bandung Regency using William N Dunn’s policy evaluation theory with the parameters of Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy. The research method used is descpritive qualitative with an inductive approach. Based on the research results, it is known that the implementation of flood disaster preparedness in Bandung Regency in terms of Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy can be said to be good with supporting and inhibiting factors. The supporting is Regional Heads in implementing disaster management as evidenced by the availability of a disaster management Task Force and the implementation of effective coordination in reducing disaster risks. Inhibiting factors are: Limited facilities and infrastructure; Lack of human resources, and Limited budget for socialization of maps of disaster prone areas. The suggestions that the author can give are: Increasing the quality and quantity of human resources, maintaining available facilities and infrastructure; and Increasing the dissemination of disaster information by utilizing social media. Keywords: Evaluation, Preparedness and Flood Disaster.